1994
DOI: 10.1128/jvi.68.1.148-157.1994
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated hepatitis A virus: genetic determinants of adaptation to growth in MRC-5 cells

Abstract: A live candidate hepatitis A virus vaccine, developed from the HM-175 strain and adapted to growth in primary African green monkey kidney (AGMK) cells, was adapted to growth in MRC-5 cells. The nucleotide sequence of the MRC-5 cell-adapted virus was determined and compared with the known sequence of the AGMK cell-adapted virus. Thirteen unique mutations, which occurred during passage in MRC-5 cells, were identified. Four of the unique mutations were located in a cluster in the 5' noncoding region (NC), and thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
53
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 27 publications
0
53
0
Order By: Relevance
“…The virus encoded by this cDNA has 21 nucleotide changes compared with the wild-type HM175 virus (8) (Fig. 2) and in cell culture (18) and in animals (5) has characteristics similar to those of the passage 32 virus (Fig. 1).…”
mentioning
confidence: 93%
See 3 more Smart Citations
“…The virus encoded by this cDNA has 21 nucleotide changes compared with the wild-type HM175 virus (8) (Fig. 2) and in cell culture (18) and in animals (5) has characteristics similar to those of the passage 32 virus (Fig. 1).…”
mentioning
confidence: 93%
“…In addition, new MRC-5-specific mutations in the 2B-2C region and a cluster of mutations acquired in the 5Ј NC region during passage in AGMK cells (bases 124, 131 to 134, 152, and 203) ( Fig. 2) were found to increase the efficiency of growth in MRC-5 cells, but only when combined with the MRC-5-specific cluster of 5Ј NC mutations (18). Studies of HAV growth in fetal rhesus kidney 4 (FRhK-4) cells previously demonstrated that a few mutations which had a major impact on growth could be functionally replaced by a large number of mutations which individually had only a small impact (14).…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…In common to PV, HAV RNA was shown to have acquired mutations in its IRES element that enhance replication by facilitating cap-independent translation in a celltype-specific fashion. Interestingly, passage of HAV in different cell types engendered different sets of mutations; however, all adaptive events were clustered within the IRES [139][140][141].…”
Section: Translational Control and Viral Pathogenesismentioning
confidence: 99%